Author Correction: Insights into isotherms, kinetics, and thermodynamics of adsorption of acid blue 113 from an aqueous solution of nutraceutical industrial fennel seed spent (Scientific Reports, (2023), 13, 1, (22665), 10.1038/s41598-023-49471-w) - Taqui S.N.; Syed A.A.; Mubarak N.M.; Farade R.A.; Khan M.A.M.; Kalam M.A.; Dehghani M.H.; Soudagar M.E.M.; Rather R.A.; Shamshuddin S.Z.M.; Karri R.R. (Nature Research, 2025)
Correction to: Scientific Reports, published online 19 December 2023 The original version of this Article omitted an affiliation for Mohammad Hadi Dehghani. The correct affiliations are listed below. Department of Environmental Health Engineering, School of Public Health, Tehran University of Medical Science, Tehran, Iran. Center for Solid Waste Research, Institute for Environmental Research, Tehran University of Medical Sciences, Tehran, Iran. In addition, Manzoore Elahi Mohammad Soudagar was incorrectly affiliated with ?Center for Solid Waste Research, Institute for Environmental Research, Tehran University of Medical Sciences, Tehran, Iran?. The original Article has been corrected. ? 2024, The Author(s).